Makrozoobentos Diversity in Various Substrates Type in Way Sindalapai River, Liwa Botanical Garden - Rani Setiana; Tugiyono Tugiyono; Gregorius Nugroho Susanto; Suratman Suratman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
The study of macrozoobenthos diversity in Way Sindalapai River can be used as one of the basic concepts in sustainable resource management in Liwa Botanical Garden area. Macrozoobenthos has an important role in the aquatic ecosystem, such as a food source for aquatic biota and as a detritivore. This study aims to determine the diversity of macrozoobenthos based on different sediment substrates in Way Sindalapai River, Liwa Botanical Garden, West Lampung. This study uses a purposive sampling method based on differences in the sediment substrates: muddy, sandy, rocky, and scrub with 3 replications. Sampling was carried out using a stratified filter and tweezers to separate the organism from the substrate. Samples were preserved in 70% alcohol and were identified by identification books at the Ecology Laboratory, FMIPA Universitas Lampung. The results of the study found 10 macrozoobenthos orders with a total of 155 individuals included in 13 families. The results of the calculation of diversity index values (H ') macrozoobenthos for all types of 2.26 (medium category). The highest macrozoobenthos dominance index (D) of the four substrates is in the rocky substrate that is 0.41 (low category). While the evenness index value (E) of macrozoobenthos in the Sindalapai Way River was 0.44 (medium category).